Sistem Informasi Pengaduan Masyarakat Berbasis Website - I Putu Krisna Megadana; I Gusti Ngurah Anom Cahyadi Putra (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2023)
Public complaints are an important mechanism in maintaining accountability of the government and other organizations, as well as strengthening relations between the government and citizens. Public complaints provide an opportunity for individuals or groups to report problems, dissatisfaction, or violations they experience related to public services, corruption, human rights violations, and so on. However, in some cases in some areas it is still difficult to make complaints about the environment that occur in the community. Therefore, we have compiled this journal with the title